2019
DOI: 10.3390/jcm8122081
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Clinicopathological Demographics of Vulvar Cancer in Japan: Increasing Oldest-Old, Stage Shifting, and Decreasing Cohort-Level Survival †

Abstract: Background: To examine trends in the clinicopathological characteristics of vulvar cancer in Japan. Methods: This is a nationwide retrospective study examining consecutive women with vulvar cancer between 2001 and 2010 in Japan (n = 1061). Temporal trends in demographics, tumor characteristics, and survival were assessed by cohort-level analysis. The National Cancer Institute’s Surveillance, Epidemiology, and End Result Program was used for external validation (n = 10,154). Results: The number of oldest-old wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
(33 reference statements)
1
17
1
Order By: Relevance
“…For instance, vulvar reconstruction per plastic surgeons is associated with adequate surgical margin [ 17 ]. Moreover, in a recent German study where the treatment volume is considerably higher than the current study (average 5–6 cases a year per a center), positive margin rate is significantly low (9.9% vs. 22.4%) [ 15 18 ]. To this end, centralizing care of vulvar cancer to the centers with adequate treatment resource and quality would be ideal to improve outcome.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…For instance, vulvar reconstruction per plastic surgeons is associated with adequate surgical margin [ 17 ]. Moreover, in a recent German study where the treatment volume is considerably higher than the current study (average 5–6 cases a year per a center), positive margin rate is significantly low (9.9% vs. 22.4%) [ 15 18 ]. To this end, centralizing care of vulvar cancer to the centers with adequate treatment resource and quality would be ideal to improve outcome.…”
mentioning
confidence: 58%
“…This is a secondary exploratory analysis of a previously organized nationwide retrospective observational study by querying the JGOG-1075S database [ 15 ]. The study protocol was approved by the ethics committee of each participating institution (hosting institution, Kurume University; Institutional Review Board registration No.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Despite advances in resuscitation therapies and techniques, the survival rate of CA remained unchanged at 8% over the past decades. 2 In addition, neurological disorders, cardiac insufficiency and other organ dysfunction after return of spontaneous circulation (ROSC) are still intractable. 3,4 Several epidemiological studies have revealed that the risk of CA increases with age.…”
Section: Introductionmentioning
confidence: 99%